Lipidomic analysis of the molecular specificity of a cholinephosphotransferase in situ. (26th October 2004) - Hunt, A.N.; Fenn, H.C.; Clark, G.T.; Wright, M.M.; Postle, A.D.; McMaster, C.R.
Abstract : Dynamic lipidomics using ESI–MS (tandem electrospray ionization mass spectrometry) of 9-deuterated choline (choline- d 9 ) incorporation into mammalian cell PtdCho (phosphatidylcholine) permits assessment of the molecular specificity of synthesis. Bulk cell PtdCho synthesis occurs in spatially distinct locations, using separate CPTs (1, 2 diacylglycerol CDP:choline cholinephosphotransferases). We assessed whether in vitro molecular selectivity of DAG (diacylglycerol) incorporation between CPTs is manifest in situ, by monitoring choline- d 9 incorporation into PtdCho and lyso-PtdCho molecular species over 3 h in control cells and in CHO-K1 cells overexpressing hCEPT1. Compared with controls, the basal molecular species composition of hCEPT1 overexpressors was significantly enriched in arachidonate. This was not due to net accretion of cellular PtdCho arguing against effects of inadequate unsaturated PtdCho degradation or remodelling. Rather, time-course analyses of PtdCho and lyso-PtdCho pools showed that both arachidonate-containing DAG incorporation and turnover of PtdCho is increased in hCEPT1 overexpressors. Increased choline- d 9 incorporation into arachidonyl lyso-PtdCho shows that both phospholipase A1 - and A2 -mediated turnover is involved. Spatially distinct molecular specificity of DAG incorporation into cellular PtdCho at the level of hCEPT1 exists in situ .